CXCL11 production in cerebrospinal fluid distinguishes herpes simplex meningitis from herpes simplex encephalitis - Liza Lind; Marie Studahl; Linn Persson Berg; Kristina Eriksson (Journal of Neuroinflammation, 2017)
Abstract Background The closely related herpes simplex viruses 1 and 2 can cause inflammations of the central nervous system (CNS), where type 1 most often manifest as encephalitis (HSE), and type 2 as meningitis (HSM). HSE is associated with severe neurological complications, while HSM is benign in adults. We proposed that studying the chemokine and cytokine production in cerebrospinal fluid (CSF) and serum could indicate why two closely related viruses exhibit different severity of their accompanied CNS inflammation. Methods Secretion patterns of 30 chemokines and 10 cytokines in CSF of adult patients with acute HSE (n = 14) and HSM (n = 20) in the initial stage of disease were analyzed and compared to control subjects without viral central nervous system infections and to levels in serum. Results Most measured chemokines and cytokines increased in CSF of HSE and HSM patients. Overall, the CSF chemokine levels were higher in CSF of HSM patients compared to HSE patients. However, only five chemokines reached levels in the CSF that exceeded those in serum facilitating a positive CSF-serum chemokine gradient. Of these, CXCL8, CXCL9, and CXCL10 were present at high levels both in HSE and HSM whereas CXCL11 and CCL8 were present in HSM alone. Several chemokines were also elevated in serum of HSE patients but only one in HSM patients. No chemokine in- or efflux between CSF and serum was indicated as the levels of chemokines in CSF and serum did not correlate. Conclusions We show that HSM is associated with a stronger and more diverse inflammatory response in the CNS compared to HSE in the initial stage of disease. The chemokine patterns were distinguished by the exclusive local CNS production of CXCL11 and CCL8 in HSM. Inflammation in HSM appears to be restricted to the CNS whereas HSE also was associated with systemic inflammation.